Editorial: Technological developments in point of interest recommendation for smart and sustainable cities - Krishna Kumar Mohbey (21324377) (2024)
Editorial: Technological developments in point of interest recommendation for smart and sustainable cities Other Information Published in: Frontiers in Sustainable Cities License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/frsc.2024.1463102